## Missing pair

First read the problem description.

Let \(n=1000000\), \(s'\) be the sum of the numbers in
input, \(s = \sum_{k=1}^n - s' =
\frac{n*(n+1)}{2} - s'\)^{1}, \(q'\) be the sum of the squares of the
numbers in input, \(q = \sum_{k=1}^n k^2 -
q' = \frac{2*n^3+3*n^2+n}{6} - q'\)^{2}

Now let \(x+y = s\) and \(x^2+y^2=q\) if we put these two equations in a system and solve it we get \(x = \frac{s + \sqrt[2]{2*q-s^2}}{2}\) and \(y = \frac{s - \sqrt[2]{2*q-s^2}}{2}\).

Sample inputs:

Source code of the solution(s):